A qualitative interview study on quality of life and ageing experiences of autistic adults - Hannah E. Viner; Nicola Yuill; Andreia P. Costa; Holly Radford; Anna E. Kornadt (Communications Psychology)
Abstract Quality of life across the lifespan has been established as a key research priority by the autism community. Still relatively little is known about the quality of life and ageing experiences of older autistic adults. Most studies to date have used generic measures of quality of life which may not accurately capture the experiences of autistic people. The aim of this qualitative study was to understand how autistic adults experience and define quality of life as they age. We conducted semi-structured interviews with 16 autistic adults aged 40+ from the UK and Luxembourg. Using reflexive thematic analysis, we identified five themes that contribute to quality of life: (1) Diagnosis is pivotal, (2) Connection with others, (3) Autonomy over space and time, (4) ‘Paperwork of life’, (5) Vulnerability. This study identifies autism-specific aspects of quality of life and highlights ways in which ageing and autism intersect and impact quality of life.